STATE SUPERVISION OVER THE LOCAL SELF-GOVERNMENT IN THE VIDOVDAN CONSTITUTION - Maksimović, Nebojiša (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The issue of the form of supervision that the state government exercises over the local self-government was topical in the period of the adoption of the Vidovdan Constitution. The paper follows its development from the constitutional drafts of Vesnić’s and Pašić’s government through amendments to the Constitutional Committee up to the final adoption in the Constituent Assembly in June 1921 and the adoption of the Law on General Administration and the Law on Regional and District Self-Governmnent. Constitutional and legal solutions that regulated the legal position of state bodies in areas and counties, local self-government bodies and their mutual relations were analyzed. State supervision over local self-government, primarily regional, is considered in the context of supervision over its acts and bodies. The supervision over regional finances is especially shown, as much because of the importance for the functioning of the regional self-government, as well as because of the restrictions to which it was exposed. The aim of the research is to point out the legal relations between the central administration and local self-government in the Kingdom of Serbs, Croats and Slovenes, established by the Vidovdan Constitution and the Law on Regional and District Self-Government.
Keywords: Vidovdan Constitution; local self-government; state supervision; control of legality and expediency